Igbo in the Atlantic World : African Origins and Diasporic Destinations - Njoku, Raphael Chijioke; Falola, Toyin (Book collections on Project MUSE., 2016)
The Igbo are one of the most populous ethnic groups in Nigeria and are perhaps best known and celebrated in the work of Chinua Achebe. In this landmark collection on Igbo society and arts, Toyin Falola and Raphael Chijioke Njoku have compiled a detailed and innovative examination of the Igbo experience in Africa and in the diaspora. Focusing on institutions and cultural practices, the volume covers the enslavement, middle passage, and American experience of the Igbo as well as their return to Africa and aspects of Igbo language, society, and cultural arts. By employing a variety of disciplinary perspectives, this volume presents a comprehensive view of how the Igbo were integrated into the Atlantic world through the slave trade and slavery, the transformations of Igbo identities and culture, and the strategies for resistance employed by the Igbo in the New World. Moving beyond descriptions of generic African experiences, this collection includes 21 essays by prominent scholars throughout the world.